Influence of percentage rationing on digestibility and nutritional performance of a pig diet - Boza, J.; Fonollá, J.; Varela, G. (Ars Pharmaceutica (Internet), 1969)
We have determined the digestibility, growth efficiency coefficient, daily increase of weight and transformation indexes of a compound food in pigs during the fattening period, using rations representing 3, 4, 5, and 6% of the weight of the animal in dry matter of the foor, with th object of determining the influence of the level of the diet on these coefficients and indexes. We have also used 2 and 4.5% rations of the weight of the animal in dry matter of the food. Four digestibility experiments, based on a latin square and using the techniques recommended by the European Federation of Zootechnia, have been carried out by the direct method. Graphs have been prepared showing the variations found in the growth and in the transformation indexes due to the different levels of diet. Lastly, we have treated our results statiscally using variance analysis, average significance test and correlation coeficients with their probable error.